High-frequency modulation of rat spinal field potentials: effects of slowly conducting muscle vs. skin afferents - Zhang, Juanjuan; Hoheisel, Ulrich; Klein, Thomas; Magerl, Walter; Mense, Siegfried; Treede, Rolf-Detlef (Journal of neurophysiology, 2016)
Long-term potentiation (LTP) in rat spinal dorsal horn neurons was induced by electrical high-frequency stimulation (HFS) of afferent C fibers. LTP is generally assumed to be a key mechanism of spinal sensitization. To determine the contribution of skin and muscle afferents to LTP induction, the sural nerve (SU, pure skin nerve) or the gastrocnemius-soleus nerve (GS, pure muscle nerve) were stimulated individually. As a measure of spinal LTP, C-fiber-induced synaptic field potentials (SFPs) evoked by the GS and by the SU were recorded in the dorsal horn. HFS induced a sustained increase of SFPs of the same nerve for at least 3 h, indicating the elicitation of homosynaptic nociceptive spinal LTP. LTP after muscle nerve stimulation (HFS to GS) was more pronounced (increase to 248%, P < 0.05) compared with LTP after skin nerve stimulation (HFS applied to SU; increase to 151% of baseline, P < 0.05). HFS applied to GS also increased the SFPs of the unconditioned SU (heterosynaptic LTP) significantly, whereas HFS applied to SU had no significant impact on the SFP evoked by the GS. Collectively, the data indicate that HFS of a muscle or skin nerve evoked nociceptive spinal LTP with large effect sizes for homosynaptic LTP (Cohen's d of 0.8-1.9) and small to medium effect sizes for heterosynaptic LTP (Cohen's d of 0.4-0.65). The finding that homosynaptic and heterosynaptic LTP after HFS of the muscle nerve were more pronounced than those after HFS of a skin nerve suggests that muscle pain may be associated with more extensive LTP than cutaneous pain.